Tantangan Pengobatan Pasien Obesitas Pada Terapi Gangguan Depresi Mayor (MDD): Laporan Kasus - Istriana, Erita; Sudarma, Verawati (Fakultas Kedokteran Universitas Trisakti, 2024)
Depression and obesity are two disorders that profoundly impact worldwide health. This is primarily because of their high occurrence, which is linked to both illness and death. Obesity increases the likelihood of developing depression and vice versa. The susceptibility to depression in individuals with obesity implies the existence of linked mechanisms between both conditions, although the molecular processes involved are not well comprehended. We describe a 28-year-old man who sought help from a dietitian or nutrition specialist to address weight gain that occurred after he began taking medication for his major depressive disorder (MDD) three years ago. This case study aims to address the challenges of treating obesity in patients with major depressive disorder (MDD) treatment.